Capacity Analysis of Gusset Plates in Truss Bridge Connections Using the Federal Highway Administration and Finite Element Methods. - Rosenstrauch, Paul. (2017)
Abstract: The 2007 collapse of the I-35W Bridge in Minneapolis, Minnesota led to additional load rating requirements for gusset plates. The Federal Highway Administration provided the direct tension and block shear methods to assess tensile capacity for use in load rating, as well as a mechanics based method to assess shear capacity on critical planes. However, the three methods provide little information about ultimate behavior for complex connections. Using finite elements, the authors modeled the connection from R.E. Whitmore's 1952 study and loaded it to failure to find the plate capacity and failure mechanism. The analysis showed that the direct tension method predicted neither capacity nor behavior. Model performance corresponded well with shear capacity on the gross horizontal plane. Yielding on this plane began around critical bolt holes and spread to either side of the plate. At capacity, the beginning of block shear failure was evident along the left diagonal.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Civil Engineering.; Advisors: Brian Brenner, and Masoud Sanayei.; Committee: Brian Brenner, Masoud Sanayei, and Erin Santini-Bell.; Keyword: Civil engineering.